Anatomical Peculiarities of Reproductive Organs of «Lycopersicon esculentum» Infected with a Severe Strain of Tobacco Mosaic Virus - Sayed, El Sayed Tarek A.; Eskarous, Josephine; El Shamy, Magdy M. (Phytopathologia Mediterranea, 2000)
The histopathology of tomato sepals, petals, anthers, ovaries and fruit pericarps infected with a highly heat resistant strain of TMV showed many peculiarities. Among these were: undulation and wrinkling of the lower epidermis of sepals and petals, presence of isthmus and failure of xylem and phloem to differentiate. The epidermal cells of the anthers were hooked, the number of pollen sacs was reduced and the vascular elements of the lower region of the fruits appeared thicker than normal, ruptured or disintegrated, and the cortical region appeared small with a wavy or ruptured layers.